2022
DOI: 10.3390/cancers14184422
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection Is Superior to TACE in the Treatment of HCC in a Well Selected Cohort of BCLC-B Elderly Patients—A Retrospective Observational Study

Abstract: Hepatocellular carcinoma (HCC) usually develops in cirrhotic liver, with high recurrence rates. However, considering its increasing detection in non-cirrhotic liver, the choice of treatment assumes particular relevance. This study aimed to investigate outcomes of patients among BCLC stages and enrolled for surgical resection (SR) according to a more complex evaluation, to establish its safety and efficacy. A total of 186 selected HCC patients (median age 73.2 yrs), submitted to SR between January 2005 and Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The BCLC system, which is widely accepted for HCC staging and the treatment selection (16), does not recommend hepatectomy for stage B disease patients. However, several studies have suggested that potentially curative treatments, such as resection, can be safe and effective for stage B disease patients (17)(18)(19). However, the use of TACE in BCLC-B patients has been questioned in recent years (20).…”
Section: Discussionmentioning
confidence: 99%
“…The BCLC system, which is widely accepted for HCC staging and the treatment selection (16), does not recommend hepatectomy for stage B disease patients. However, several studies have suggested that potentially curative treatments, such as resection, can be safe and effective for stage B disease patients (17)(18)(19). However, the use of TACE in BCLC-B patients has been questioned in recent years (20).…”
Section: Discussionmentioning
confidence: 99%
“…Child-Pugh grade A and B, indocyanine green retention rate at 15 min of 20-30%, and the estimated remnant liver volume of≥35% are listed as prerequisites for resection. Locoregional therapy such as bland hepatic artery embolization, transarterial chemoembolization, and drug-eluting bead transarterial chemoembolization, were used for patients with advanced or unresectable disease who are not surgical candidates (11)(12)(13).…”
Section: Liver Resectionmentioning
confidence: 99%